Estimated carotid-femoral pulse wave velocity has similar predictive value as measured carotid-femoral pulse wave velocity - Greve, Sara V; Blicher, Marie K; Kruger, Ruan; Sehestedt, Thomas; Gram-Kampmann, Eva; Rasmussen, Susanne; Vishram, Julie K K; Boutouyrie, Pierre; Laurent, Stephane; Olsen, Michael H (Journal of hypertension, 2016)
Carotid-femoral pulse wave velocity (cfPWV) adds significantly to traditional cardiovascular risk prediction, but is not widely available. Therefore, it would be helpful if cfPWV could be replaced by an estimated carotid-femoral pulse wave velocity (ePWV) using age and mean blood pressure, and previously published equations. The aim of this study was to investigate whether ePWV could predict cardiovascular events independently of traditional cardiovascular risk factors and/or cfPWV. cfPWV was measured and ePWV was calculated in 2366 patients from four age groups of the Danish MONICA10 cohort. Additionally, the patients were divided into four cardiovascular risk groups based on Systematic COronary Risk Evaluation (SCORE) or Framingham risk score (FRS). In 2006, the combined cardiovascular endpoint of cardiovascular death, nonfatal myocardial infarction, stroke and hospitalization for ischemic heart disease was registered. Most results were retested in 1045 hypertensive patients from a Paris cohort. Bland-Altman plot demonstrated a relative difference of -0.3% [95% confidence interval (CI) -15 to 17%] between ePWV and cfPWV. In Cox regression models in apparently healthy patients, ePWV and cfPWV (per SD) added independently to SCORE in prediction of combined endpoint [hazard ratio (95%CI) = 1.38(1.09-1.76) and hazard ratio (95%CI) = 1.18(1.01-1.38)] and to FRS [hazard ratio (95%CI) = 1.33(1.06-1.66) and hazard ratio (95%CI) = 1.16(0.99-1.37)]. If healthy patients with ePWV and/or cfPWV at least 10 m/s were reclassified to a higher SCORE risk category, net reclassification index was 10.8%, P less than 0.01. These results were reproduced in the Paris cohort. ePWV predicted major cardiovascular events independently of SCORE, FRS and cfPWV indicating that these traditional risk scores have underestimated the complicated impact of age and blood pressure on arterial stiffness and cardiovascular risk.